Surgical Revascularization of the Dual Left Anterior Descending Coronary Artery; A Case Report - Imtiaz Ahmed Chaudhry; Mehwish Naseer; Fakhar-e- Fayyaz; Muhammad Adnan Akram; Rehana Javaid (Pakistan Armed Forces Medical Journal, 2022)
Although dual left anterior descending arteries are found in about 1% of the population, identification and localization of these coronaries remains a challenge for cardiac surgeons throughout coronary artery bypass graft surgery. We present a case of dual left anterior descending (LAD) coronary artery disease and highlight the techniques used for identifying these vessels.